Pokémon. Sun & Moon. 6 - Kusaka, Hidenori; Turnage, Bryant (VIZ Media, LLC, 2020)
Sun is now getting paid to find Zygarde Cells throughout Alola. Then, Sun gets in the middle of a battle between trial captains and the Ultra Beasts who are attacking from a rift in the sky.